Foreign Body Granulomas after the Use of Dermal Fillers: Pathophysiology, Clinical Appearance, Histologic Features, and Treatment - Jeong Min Lee; Yu Jin Kim (Archives of Plastic Surgery, 2015)
A foreign body granuloma is a non-allergic chronic inflammatory reaction that is mainly composed of multinucleated giant cells. Foreign body granulomas may occur after the administration of any dermal filler. Factors such as the volume of the injection, impurities present in the fillers, and the physical properties of fillers affect granuloma formation. The formation of granulomas involves five phases: protein adsorption, macrophage adhesion, macrophage fusion, and crosstalk. The clinical and pathologic features of granulomas vary depending on the type of filler that causes them. Foreign body granulomas can be treated effectively with intralesional corticosteroid injections. Surgical excisions of granulomas tend to be incomplete because granulomas have ill-defined borders and moreover, surgical excisions may leave scars and deformities.